The Effect of Compensation on Employee Performance on PT. Waskita Beton Precast TBK - Zalne, Ziola; Albani, Muhammad Hudzaifa; Tanty, Heruna (LPPM Universitas Bina Bangsa, 2023)
This study aims to analyze the effect of Compensation on employee performance of PT. Waskita Beton Precast, Tbk. There is an independent variable of the effect of Compensation to be tested for the influence on the dependent variable, namely Karyawa Performance. The population in this study were employees of PT. Waskita Beton Precast, Tbk Human Resources division which has 50 employees as of May 2020, which are all permanent employees. The research data used are primary data obtained through the dissemination of questionnaires. The analysis tool used is a simple linear regression test. The results showed that: (1) the results showed that compensation had a positive and significant effect on employee performance with a significance value of 0.022 < 0.05; (2) the test results of the coefficient of determination showed that the Adjusted R Square value of 0.579 means that as many as 57.9% of employee performance-bound variables can be explained by the free variable, namely compensation, while other factors of 42.1% were influenced by other variables outside the variables studied